Passion and reason - Lazarus, Richard S. (Oxofrd University Press, 1994)
When Oxford published Emotion and Adaptation, the landmark 1991 book on the psychology of emotion by internationally acclaimed stress and coping expert Richard Lazarus, Contemporary Psychology welcomed it as "a brightly shining star in the galaxy of such volumes." Psychiatrists, psychologists and researchers hailed it as a masterpiece, a major breakthrough in our understanding of the emotional process and its central role in our adaptation as individuals and as a species. What was still needed, however, was a book for general readers and health care practitioners that would dispel the myths still surrounding cultural beliefs about emotion and systematically explain the relevance of the new research to the emotional dramas of our everyday lives